(untitled) (Research, Society and Development, 2021)
Objective: to investigate how nurses from Basic Health Units (UBS) in the municipality of Cáceres-MT perform prenatal care for their partner, what their conceptions are and the main challenges encountered in caring for men. Method: this is a descriptive field study with a qualitative approach, carried out in July 2019, with professional nurses who work in Basic Health Units (UBS) in the municipality of Cáceres-MT. For data analysis, the content analysis technique, described by Minayo (2013), was used. Results: of the eleven nurses interviewed, only four stated that they perform the partner’s prenatal care, the following actions / procedures were evidenced: request for exams, vaccination and guidance. Conclusion: it was found that the performance of the partner’s prenatal care is still a poorly consolidated strategy in the health services of the municipality of Cáceres-MT. Professionals have knowledge about the partner’s prenatal care and recognize the benefits of this strategy, however they find it difficult to carry it out.